2014
DOI: 10.1155/2014/492173
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Extract SH003 Suppresses Tumor Growth and Metastasis of MDA-MB-231 Breast Cancer Cells by Inhibiting STAT3-IL-6 Signaling

Abstract: Cancer inflammation promotes cancer progression, resulting in a high risk of cancer. Here, we demonstrate that our new herbal extract, SH003, suppresses both tumor growth and metastasis of MDA-MB-231 breast cancer cells via inhibiting STAT3-IL-6 signaling path. Our new herbal formula, SH003, mixed extract from Astragalus membranaceus, Angelica gigas, and Trichosanthes kirilowii Maximowicz, suppressed MDA-MB-231 tumor growth and lung metastasis in vivo and reduced the viability and metastatic abilities of MDA-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 44 publications
4
70
0
1
Order By: Relevance
“…Moreover, SH003 inhibited the interaction between VEGF and VEGFR1, while the inhibitions showed different IC 50 values (Figure 5B). We recently confirmed that SH003 and its herbal components contained cucurbitacin D, decursin, formononetin, and nodakenin [13]. Therefore, we further examined whether those chemical compounds inhibits VEGF binding to VEGFR2.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Moreover, SH003 inhibited the interaction between VEGF and VEGFR1, while the inhibitions showed different IC 50 values (Figure 5B). We recently confirmed that SH003 and its herbal components contained cucurbitacin D, decursin, formononetin, and nodakenin [13]. Therefore, we further examined whether those chemical compounds inhibits VEGF binding to VEGFR2.…”
Section: Resultsmentioning
confidence: 93%
“…Our previous study showed that SH003 at higher concentrations caused breast cancer cell death by inhibiting STAT3-mediated signaling pathway [13]. SH003 concentrations tested in this study was lowered than those in the previous study [13], as we considered the metronomic approach to target tumor angiogenesis [4850].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent data have demonstrated that IL-6 induced MDA-MB-231 cell invasion via the STAT-3 signaling pathway. 40) Moreover, inhibition of IL-6 signaling has been shown to attenuate tumor growth and angiogenesis and metastatic events in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%